Analysis of Consumer Attitude Bonds with LPG Gas Purchase Decisions at PT. Mandiri Tebatkubu Village, Manna City District, South Bengkulu Regency - Wedo Handika Saputra; Ida Anggriani; Abdul Rahman (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2021)
The purpose of the study is to determine the relationship between consumer behavior and the decision to purchase LPG gas at PT. MANDIRI Tebat Kubu Village, Manna City Sub- District, South Bengkulu Regency. The sample in this study was 80 people from Tebat Kubu Village, South Bengkulu Regency. Because all the populations in this study were sampled, the sampling method used was the slovin method. The informasi collection method used was observation and questionnaires and analyzed through validity testing, reliability testing, spearman rank correlation, and hypothesis testing. Consumer behavior with purchasing decisions has a moderate correlation because the number 0. 58 is in the interval 0. 40- 0. 588. This shows that there is a moderate correlation between consumer behavior and purchasing decisions at PT. MANDIRI Tebat Kubu Village, Manna City Sub- District, South Bengkulu Regency. The result of the hypothesis of the relationship between consumer behavior and purchasing decisions is that the t_count value is much greater than the t_table value( 6. 35>1. 66), meaning that there is a significant relationship between the purchasing decision variables and the consumer behavior variables at PT. MANDIRI in South Bengkulu.